Contribuições para o ensino-aprendizagem intercultural do português língua estrangeira (PLE) : a tessitura textual por formas remissivas lexicais - Oliveira, Elynne Gabrielle Moreira de (2015)
This research deals with the local coherence by lexical remission, as one of the fundamental resources for teaching and learning Portuguese as a Foreign Language (PLE), through the Communicative approach with an intercultural bias for reading and text interpretation. It advocates that interlexical relations are the main responsible for the organization of linguistic and extralinguistic skills in order (re)build textual-discursive meanings. Based on the theoretical and methodological foundations of sociocognitive and interactional Textual Linguistics, interfaced with assumptions of Lexicology, the objective is to verify if the teaching manual “Bem-vindo! A língua portuguesa no mundo da comunicação”, whose target audience is the PLE learner, fulfills its didactic and pedagogical communicative proposal, whose unit of analysis is the text. Therefore, texts were selected from this manual, in order to verify the theoretical treatment concerning the teaching of reading and text interpretation, based on the procedures of textual coherence by remissive lexical forms. The results obtained by the corpus of analysis point to a high degree of inconsistency between the communicative proposal of the textbook and its effective theoretical and methodological work concerning texts for reading and interpretation purposes. The analyzes, using the resources of local coherence by remissive lexical forms, not only allow to identify such incongruity but also provide contributions to the teaching-learning PLE, in order to enrich the communicative approach associated with elements that offer new pathways for interculturality, mostly for providing the apprentice with (re)construction of other / new sociocultural representations, through the activation of social cognition marks and the mental models suited to the origin culture in interaction with socio-cognitive models and marks in target culture.